Effects of pre-germination treatments in overcoming rice seed dormancy and on the enzymatic activity of peroxidase - Vieira, Antonio Rodrigues; Vieira, Maria das Graças Guimarães Carvalho; de Carvalho, Vania Dea; Fraga, Antonio Carlos (Pesquisa Agropecuaria Brasileira, 1994)
This work was developed under laboratory conditions, at Escola Superior de Agricultura de Lavras, in 1989/90 to evaluate the efficiency of pre-germination treatments in overcoming rice (Oryza sativa L.) seed dormancy, as well as their effects on peroxidase enzyme activity. Irrigated cultivars Inca and MG I, both presenting post-harvest dormancy, were submitted to different treatments prior to germination: 1% sodium hipochlorite; hidrogen peroxide (H2O2 - 20 Vol.); accelerated aging 40°C and 100% UR; and pre-drying, in an oven with forced air circulation at different time x temperature combinations. Pre-drying at 40°C for 168 hours presented the best results in overcoming seed dormancy of both cultivars. Pre-drying treatments were also more effective in inhibiting peroxidase activity, especially for cultivar Inca.